Empowering teenagers as health cadres to prevent non-communicable diseases in dusun Jaten, Sleman, DI Yogyakarta - Melyza Perdana (Berita Kedokteran Masyarakat (BKM), 2018)
Objectives: Non-communicable diseases (NCDs) is increasing worldwide. Particularly in Yogyakarta, the prevalence of some NCDs even the highest in Indonesia. Dusun Jaten, as one of practicum field for CFHC-IPE FK-KMK UGM also found the same problem. It was reported that hypertension and diabetes are the most common health problem in community. Actually, in 2009 Indonesian Ministry of Health initiated POSBINDU PTM. However, only some villages has launched POSBINDU PTM and only a few villages raising awareness of NCDs since young age. Thus, in 2017 we initiated a POSBINDU PTM Program in Dusun Jaten together with Puskesmas Mlati 1, RS UGM, and Sleman Health District. This program aimed to build awareness and increase the participation of teenagers in preventing NCDs. Contents: We started the program by conducting a survey among Jaten residents related to POSBINDU PTM. Interestingly, almost 100% of Jaten residents were not familiar with POSBINDU PTM. Following this further, we recruited health cadres as many as 30 new health cadres (male and female) and 40 % of them are teenagers. After that we started a series “Sekolah Kader” program. A semi structure interview was done among teenagers health cadre related to evaluate the knowledge, skills, and willingness to participate in POSBINDU PTM. Many teenager health cadres were satisfied of the program and they also made a good system in managing POSBINDU. POSBINDU PTM Jaten was lauched in February 2018. Since then, more than 75 residents attended POSBINDU program, not only older adult but also young adult. And this number is increasing every month. It can be concluded that involving teenager health cadres could be an important step to prevent NCDs by increasing the awareness of young adult to participate in regular health check up at POSBINDU PTM.